Reputation: 3689
My source xml file has elements in this form:
<field name="Address1">Address1Value</field>
<field name="Address2">Address2Value</field>
<field name="Address3">Address3Value</field>
I need to merge these into a single element, thus:
<field name="Address">Address1Value\r\nAddress2Value\r\nAddress3Value</field>
I know how to get the value of the Address1 element (as below), I just can't figure out how to augment it with the other two. How can I do this?
<xsl:template match="field[@name = 'Address1']">
<field>
<xsl:attribute name="name">Address</xsl:attribute>
<xsl:value-of select="concat(., 'how-do-I-get-the-values-of-Address2-and-Address-here3?')"/>
</field>
</xsl:template>
Upvotes: 3
Views: 18957
Reputation: 19194
You can make it a little more generic like this (given the parent of field elements is fields):
<xsl:stylesheet xmlns:xsl="http://www.w3.org/1999/XSL/Transform" version="1.0">
<xsl:template match="fields">
<field>
<xsl:attribute name="name">Address</xsl:attribute>
<xsl:apply-templates select="node()"/>
</field>
</xsl:template>
<xsl:template match="field[starts-with(@name, 'Address')]">
<xsl:value-of select="concat(.,'\r\n')"/></xsl:template>
</xsl:stylesheet>
Upvotes: 5
Reputation: 3689
I worked it out, like this:
<xsl:value-of select="concat(., ../field[@name = 'Address2'], ../field[@name = 'Address3'])"/>
Upvotes: 1